Implementation of Clinical Supervision in Improving the Quality of Teacher Performance at Madrasah Ibtidaiyah - Nasution, Toni; Syafaruddin, Syafaruddin; Syukri, Makmur (Universitas Pahlawan Tuanku Tambusai, 2021)
Clinical supervision is an important part of the management aspect in an effort to oversee the implementation of education (from managerial and academic aspects) to improve quality (processes and services) in educational institutions. This article aims to help or facilitate the schools and teachers of MIS Al-Ittihadiyah Pangkalan Mansyur in order to carry out their duties and responsibilities to the fullest. This study uses a descriptive qualitative approach. This means using a case study research design with a supervision instrument. So in analyzing it, the author uses interactive model data analysis, namely data reduction, data display and conclusion drawing/verification. This study shows that the implementation of clinical supervision in improving the quality of teacher performance at MIS Al-Ittihadiyah must be thoroughly reviewed, so that it can create qualified and competent and competitive teachers in the future. So as to be able to create human resources in accordance with the needs of the 21st century